1997
DOI: 10.1007/s002329900197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Important Amino Acid Residues of the Na + -Ca 2+ Exchanger Inhibitory Peptide, XIP

Abstract: The Na+-Ca2+ exchanger plays an important role in cardiac contractility by moving Ca2+ across the plasma membrane during excitation-contraction coupling. A 20 amino acid peptide, XIP, synthesized to mimic a region of the exchanger, inhibits exchange activity. We identify here amino acid residues important for inhibitory function. Effects of modified peptides on Na+-Ca2+ exchange activity were determined. Exchange activity was assessed as 45Ca2+ uptake into Na+-loaded cardiac sarcolemmal vesicles. We find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…The list of agents employed includes many different cationic peptides and the aminoglycosides. The cationic peptides include two putatively specific inhibitors of NCX1, the "XIP" peptide that represents a sequence from the exchanger itself [32], and a cyclic cationic peptide found to be a strong exchanger inhibitor [45]. These peptides inhibit the PIP 2 -sensitive KATP channels almost equally powerfully as they inhibit Na/Ca exchange (not shown), suggesting that PIP 2 -binding may indeed play a role.…”
Section: Ion Channel and Transporter Regulationmentioning
confidence: 97%
“…The list of agents employed includes many different cationic peptides and the aminoglycosides. The cationic peptides include two putatively specific inhibitors of NCX1, the "XIP" peptide that represents a sequence from the exchanger itself [32], and a cyclic cationic peptide found to be a strong exchanger inhibitor [45]. These peptides inhibit the PIP 2 -sensitive KATP channels almost equally powerfully as they inhibit Na/Ca exchange (not shown), suggesting that PIP 2 -binding may indeed play a role.…”
Section: Ion Channel and Transporter Regulationmentioning
confidence: 97%
“…XIP is an autoregulatory region of the intracellular loop of the NCX protein that effectively inhibits NCX activity. [41][42][43][44] Exogenous XIP can act as a specific NCX inhibitor. Intracellular sodium binds to the XIP region and induces NCX inactivation, while increasing intracellular calcium, via a separate binding site, promotes NCX activation by alleviating sodium inactivation.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…Mutations that eliminate inactivation produce stronger interactions between phosphatidylinositol 4,5-bisphosphate [PtdIns(4,5)P 2 ] and XIP, whereas those interactions are weakened by mutations that promote inactivation (116,176). Mutations in the XIP peptide indicate that although its full length is required for maximal potency, the more relevant inhibitory components are basic and aromatic residues between positions 5 and 16 (117). A recent work claims that in NCX the binding site for XIP may be located in the loop zone between amino acids 562 and 679 (171); at any rate, although the site of interaction of the XIP region with the rest of the NCX molecule has not been identified, it has been suggested that this region functions as an auto inhibitory domain that shifts the active-inactive states of the Na ϩ /Ca 2ϩ exchanger.…”
Section: Na I ϩ -Dependent Inactivationmentioning
confidence: 99%